Taguchis Quality Improvement Analysis of the SME Bread Manufacturing - Sihombing, Haeryip; M.K., Hafiz; M.Y. , Yuhazri (Getview, 2012)
The purpose of this study is to optimize the manufacturing process of the SME bread product using Taguchi method. The study is focused on the quality problems occurred as the outcomes of the process (quality of the bun produced) related to controllable factors of products design identified (machine temperature and length duration time) for the improvement required. By implementing the technique of analysis of variance (ANOVA), the composition of the controlled parameters, such as machine temperatures and duration times, is therefore determined and constructed into Orthogonal Array (OA) of L9(33) related to what the setting parameters produces the optimal output. To improve the quality of the manufactured product, the setting of parameter recommended in this study is A2B2C2 or A1B2C2 {(Low or High) ∩ 10minutes ∩ 200OC)}.